Simultaneous determination of levothyroxine and its metabolite liothyronine in human serum by using LC-ESI-MS/MS and its bioequivalence application - Kanchan Soni,, Gopal Prasad Agrawal (Journal of Applied Pharmaceutical Science, 2024)
Levothyroxine is a synthetic thyroid hormone, used to treat hypothyroidism and related conditions. It has been a widely used and effective medication for many decades. The bioanalytical method is developed for the determination of endogenously present levothyroxine and its metabolite, liothyronine, in both stripped and un-stripped serum, using liquid chromatography-tandem mass spectrometry. Determining an endogenously present analyte is indeed a critical step in pharmacokinetic studies and determining the therapeutic dose of a drug. The term “stripped” typically refers to the removal of endogenous analytes that interfere with the accurate quantification of the analyte of interest. Method employed with, Kinetex® polar C18 (100 × 4.6 mm 2.6 μm) analytical column for chromatographic resolution by using, pump A as acetic acid in water and pump B as acetic acid in methanol. The mass spectrometer used with triple quadrupole operating in the positive ion mode, specifically using multiple reaction monitoring. Multiple reaction monitorin is a highly delicate and discriminating technique for quantifying specific analytes. The transitions are as follows: analyte transition: 777.55→731.65, metabolite transition: 651.70→605.85, IS analyteTransition: 780.60→734.75, and IS metaboliteTransition: 661.60→614.65. A resolution factor of 0.5 was achieved for levothyroxine and liothyronine. Linearity for levothyroxine in a range of 20.0–1000 ng/ml and liothyronine in a range of 0.3–15.0 ng/ml was employed. Method validation was performed to conduct stability studies and demonstrate the reproducibility for accuracy and reliability for LC-ESI-MS/MS assay. The proposed bioanalytical method is highly sensitive and selective, has a minimal processing volume, faster run time, no matrix impact, and the ability to measure analytes in different types of serum (stripped and normal). The method was valuable for both research and clinical laboratories and can provide reliable results.
Keywords: Endogenous, levothyroxine, liothyronine, metabolism, stripped serum